Function spaces on the Koch curve - Maryia Kabanava (Journal of Function Spaces and Applications)
We consider two types of Besov spaces on the Koch curve, defined by traces and with the help of the snowflaked transform. We compare these spaces and give their characterization in terms of Daubechies wavelets.